Exploring the Ecological Structure of Agricultural Industry School Partnership Systems in the Gippsland Region, Australia - Molly O’Dea; Amy Cosby; Jaime Manning; Nicole McDonald; Bobby Harreveld (Agriculture, 2024)
This paper aims to explore the structure of agricultural industry school partnerships (ISPs) by applying Bronfenbrenner’s ecological systems theory to partnerships delivered in Gippsland, Australia. Agricultural ISPs are one potential setting for industry-relevant learning and career education to occur. This may assist in alleviating agricultural workforce shortages and addressing educational issues related to student career outcomes. A mixed methods case study methodology was employed, with data analyzed through frequency counts and Braun and Clarke’s method of thematic analysis. Surveys (n = 111) and semi-structured interviews (n = 57 pre-participation, n = 68 post-participation) were used with educators (n = 56) and industry participants (n = 62) from ISPs delivered through CQUniversity Australia’s Raising Aspirations in Careers and Education—Gippsland project from 2021–2023. This research finds that the agricultural ISPs studied function as interdependent ecological systems. The facilitator played a crucial role in delivering the ISPs, including connecting educators and industry partners. The study is limited by the number of agricultural ISPs explored and by only collecting data from two stakeholders within the system. However, these findings contribute to a greater understanding of the complex structure of agricultural ISPs, which can help those creating ISPs to consider and understand all stakeholders’ needs. Exploring ISPs as ecological systems also provides a lens to approach research improving similar educational practices. Further research could deepen our understanding of these systems.